Symposium on rail links to the Channel Tunnel to be held at the Institution of Civil Engineers, 12-2:30 pm Thursday 31 October 1991 : background briefing paper. (Thomas Telford, 1991)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.
Keywords: Railroad tunnels -- English Channel -- Congresses.; Railroads -- England, South East -- Congresses.; Channel Tunnel (England and France) -- Congresses.; elektronické knihy; electronic books